Islamic Financial Research Directions During Pandemic: A Bibliometric Analysis - Muhamad Subhi Apriantoro; Rashifahunnisa' Mellinia; Shafy Garneta Maheswari; Hudaifah Hudaifah (Islamic Economics and Business Faculty of UIN Antasari, 2022)
This study aims to determine the direction of development of Islamic finance research during the pandemic, focusing on the growth of international publications in the field of Islamic finance in the Scopus database between 2020 and 2022. Bibliometric mapping consists of core journals in international publications in the field of Islamic finance, the productivity of researchers in the field of Islamic finance, the number of publications based on institutional collaboration in international publications in the field of Islamic finance, the development of international publications on research in the field of Islamic finance by subject/field, and a map of the development of international publications on research in the field of Islamic finance.